2017
DOI: 10.4028/www.scientific.net/msf.888.66
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sintering Temperatures on Microstructure, Porosity and Mechanical Strength of Refractory Brick

Abstract: Riyom clay sample was investigated and have porosity of 18.6 %, firing shrinkage of 7.8 %, bulk density 2.2 g/cm3 and cold crushing strength. Chemical composition was analyzed using the XRF. The refractoriness of the fireclay was 1621 °C. The thermal shock resistance was up to 25 cycles. The apparent porosity fell within the standard value of 10-30 % for refractory fireclay bricks. The investigation proved that the Riyom clay deposit belong to the alumino-silicate group of bricks. The clay is therefore, suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…The mineralogical and physical properties and mechanical strength of the fired clay bricks are generally interrelated to each others. It is reported that the firing temperature is one of the key factor to modulate the physical, sintering and mechanical properties of different types of brick samples (Ajala et al 2017a(Ajala et al , 2017bVelraj et al 2009;Karaman et al 2006), but not the firing rate on kaolinite based ceramics (Njoya et al 2017). Different physico-sintering properties (i. e., water absorption capacity, apparent porosity, apparent density, bulk density and so on) of clay bricks and their mechanical properties were investigated at different firing temperatures and the brick sample fired at 1100 °C showed the best mechanical properties (Martin-Marquez et al 2010;Ghorbel et al 2008;Yongue-Fouateu et al 2016;Johari et al 2010).…”
Section: Introduction and Objectivementioning
confidence: 99%
“…The mineralogical and physical properties and mechanical strength of the fired clay bricks are generally interrelated to each others. It is reported that the firing temperature is one of the key factor to modulate the physical, sintering and mechanical properties of different types of brick samples (Ajala et al 2017a(Ajala et al , 2017bVelraj et al 2009;Karaman et al 2006), but not the firing rate on kaolinite based ceramics (Njoya et al 2017). Different physico-sintering properties (i. e., water absorption capacity, apparent porosity, apparent density, bulk density and so on) of clay bricks and their mechanical properties were investigated at different firing temperatures and the brick sample fired at 1100 °C showed the best mechanical properties (Martin-Marquez et al 2010;Ghorbel et al 2008;Yongue-Fouateu et al 2016;Johari et al 2010).…”
Section: Introduction and Objectivementioning
confidence: 99%
“…In the chemical composition result as presented in Table 1 showed that the dominant oxides in the clay are SiO2 and Al2O3 with 2.56 % of impurities and can be categorized as alumino-silicate fireclay brick. The Alkaleri clay is in the range of chemical composition of 65-80 % SiO2 and 18-30 % Al2O3 which are classified as high duty (Siliceous) refractory fireclay brick [2,6,12]. The Gombe clay is suitable for production of furnace linings (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The particle size percentile was 4.4 %. The particle size of Alkaleri clay contributed to the mechanical strength of the fireclay because the smaller the particle sizes the more the bonding of the structural clay [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…What is more, the quality and durability assessments of different clay bricks principally based on their essential mineralogical phase, physico-sintering, and mechanical properties. It said that the best quality of the ceramic bodies also depends on the uses of clay types [2][3][4], and firing temperature [5][6][7][8] and conditions [9,10] during their production time because these parameters are critical factors to modulate different physico-mechanical properties of the ceramic bodies. A series of mineralogical phase transformation occurs during the firing of natural clay materials [11,12].…”
Section: Introductionmentioning
confidence: 99%